Perancangan Crane Untuk Mengangkat Engine Mobil Dengan Pertimbangan Ilmu Ergonomi - Hidayat, Rahmat; Arief, Dodi Sofyan; Akbar, Mustafa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Crane lifting equipment widely has been used in the world of industry and automotive. In the automotive industries, the crane is used to lift car engines and other similar proposed. In the design of this is required an ergonomics study of knowledge and the relationship between humans and machines, the interface between them. The purpose of this research is to produce a crane design to lift the car engine which structural analysis using the simulation on Autodest Inventor software and produce a crane design with consideration of ergonomics. In the design restricted crane design using software autodest inventor and engine period used maximum 300 kg, on crane design with consideration of ergonomics science only discussing of the force of the crank, the position of attraction and the position of thrust. The frame design process starts from choosing the frame form, followed by simulation on Autodesk Inventor. While the process for consideration of science carried out manual calculations. Based on crane frame simulation results was obtained minimum safety factor value of 2.72. In the position of push and pull handlebar which safe consideration was in obtained the same value that was at 68 cm slopes. It is concluded the framework still safe and the force gained for cranking that is not too heavy, in the process of pushing and pulling the instrument easily moved.Keywords : crane, ergonomics, simulation inventor and safety factor